2023
DOI: 10.1039/d3cp02990e
|View full text |Cite
|
Sign up to set email alerts
|

Conducting 1D nanostructures from light-stimulated copper-metalated porphyrin–dibenzothiophene

Yelukala Ramakrishna,
Madarapu Naresh,
Botta Bhavani
et al.

Abstract: Control over the dimensionality from stimulated organic semiconductors has shown significant interest in organic electronics; however, designing of such materials still remains decisive. Herein, we have developed three dibenzothiophene appended...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…S20 and S21†). 65 Later, activation energy ( E a ) was calculated from the above graph, and it revealed that E a is low for PA , indicating high conductivity as per the known inverse relationship between activation energy and conductivity. Whereas for PB and PA + PB , the values are high and medium, resulting in low and transitional conductivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S20 and S21†). 65 Later, activation energy ( E a ) was calculated from the above graph, and it revealed that E a is low for PA , indicating high conductivity as per the known inverse relationship between activation energy and conductivity. Whereas for PB and PA + PB , the values are high and medium, resulting in low and transitional conductivity (Fig.…”
Section: Resultsmentioning
confidence: 99%